Empirical Analysis of the Nexus between Budget Implementation and Economic Development in Nigeria (Global Journal of Management and Business Research, 2016)
The study evaluated the effect of budget implementation on Nigeria's economic growth. Gross Domestic Product (GDP) was used as the explained variable while Public Recurrent Expenditure (PRE), Public Capital expenditure, (PCE) and Public Debt Service (PDS) were used as the explanatory variables of the study. Data on these variables were sourced from the Central Bank of Nigeria statistical bulletin from 1986 to 2014. The study adopted Ordinary Least Square (OLS), Co-integration and Error Correction Model (ECM) in analyzing respectively the short and long-run effect of budget implementation on Nigeria's economic growth. The findings from the study revealed that in the short run, PRE will have a positive relationship with GDP while PCE and PDS will have a negative relationship with GDP. In the long run, there was a complete turn of relationship as to what was obtained in the short run. In both the long run and short run, only PRE is statistically significant at 5% level of significance. The F-test revealed that the overall model is statistically significant in the explanation of the subject matter. The Durbin Watson graph shows that there is absence of serial correlation in the model adopted for the study.
Keywords: budget; debt service; capital expenditure; recurrent expenditure; economic growth